MIGRASI MEDIA TELEVISI MAINSTREAM KE DIGITAL - Syintia Nurfitria; Muhamad Yusuf; Ican Mandala (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
Digital era has influenced most local television to retreat in media and also factors such as human resources and production financing are thing that hinder growth of local television in entering digital system. However, since the issuance of Law no. 32 of 2002 about Broadcasting, ownership of local television station in Indonesia is increasing. This law can be a rule as well as a protector for diversity of content and ownership of local television station in maintaining their existence. Local television existences have an important role in changing function of mainstream media, especially in raising local issues. The presence of local television expected to display regional culture, local event, or region identity, as well as live of surrounding public. Thus, local television can represent overall local cultural identity based on local wisdom while still existing with digital.